SYSTEMATIC LITERATURE REVIEW (SLR) SISTEM POWERTRAIN PADA KENDARAAN RINGAN DENGAN FOKUS PADA PENGURANGAN BOBOT DAN BIAYA - Ahmad Rafiq Ramadhan; Rafi Fauzan, Najwan; Ardiyan Saputra, Sandi; Suprayudha, Galih; Hendra Satya Saputra, Kurniawan (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze strategies for reducing weight and cost in light vehicle powertrain systems using the Systematic Literature Review (SLR) method. Based on a review of 15 indexed journals, it was found that innovative approaches in materials, design, and technology are key to achieving efficiency. The use of lightweight materials such as aluminum alloys, carbon fiber composites, and high-performance polymers has been proven to reduce weight by 30-45% while lowering production costs. Modular design optimization and component configuration (e.g., engine, transmission, battery) can improve energy efficiency, while the integration of electrification technologies (hybrid and electric) reduces energy consumption to 100 Wh/km compared to conventional vehicles (350-400 Wh/km). Physics-based modeling and Pareto analysis also play a crucial role in designing systems that balance weight, cost, and performance. However, challenges such as high initial costs and trade-offs between parameters still need to be addressed through further research. The findings of this SLR provide recommendations for the automotive industry to develop more economical, lightweight, and sustainable powertrains.